A High‐Performance Sodium‐Ion Hybrid Capacitor Constructed by Metal–Organic Framework–Derived Anode and Cathode Materials. (27th May 2018) - Li, Hongxia; Lang, Junwei; Lei, Shulai; Chen, Jiangtao; Wang, Kunjie; Liu, Lingyang; Zhang, Tianyun; Liu, Weisheng; Yan, Xingbin
Abstract: Sodium‐ion hybrid capacitors (SIHCs) can potentially combine the virtues of high‐energy density of batteries and high‐power output as well as long cycle life of capacitors in one device. The key point of constructing a high‐performance SIHC is to couple appropriate anode and cathode materials, which can well match in capacity and kinetics behavior simultaneously. In this work, a novel SIHC, coupling a titanium dioxide/carbon nanocomposite (TiO2 /C) anode with a 3D nanoporous carbon cathode, which are both prepared from metal–organic frameworks (MOFs, MIL‐125 (Ti) and ZIF‐8, respectively), is designed and fabricated. The robust architecture and extrinsic pseudocapacitance of TiO2 /C nanocomposite contribute to the excellent cyclic stability and rate capability in half‐cell. Hierarchical 3D nanoporous carbon displays superior capacity and rate performance. Benefiting from the merits of structures and performances of anode and cathode materials, the as‐built SIHC achieves a high energy density of 142.7 W h kg −1 and a high power output of 25 kW kg −1 within 1–4 V, as well as an outstanding life span of 10 000 cycles with over 90% of the capacity retention. The results make it competitive in high energy and power–required electricity storage applications. Abstract : A novel sodium‐ion hybrid capacitor is constructed by coupling a metal–organic framework (MOF)–derived TiO2 /C anode with a MOF–derived nanoporous carbon cathode. Benefitting from the effective matching in both kinetics and capacity, the device can achieve high‐energy and high‐power output as well as outstanding cyclability.